2014
DOI: 10.1063/1.4863741
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of four resistance states and exchange bias in La0.6Sr0.4MnO3/BiFeO3/La0.6Sr0.4MnO3 multiferroic tunnel junction

Abstract: The ferroelectric and tunnel electro- and magnetoresistance properties in La0.6Sr0.4MnO3/BiFeO3/La0.6Sr0.4MnO3 multiferroic tunnel junctions sandwiched with the antiferromagnetic-ferroelectric BiFeO3 as a tunnel barrier were reported. Besides the four non-volatile resistance states and the interfacial magnetoelectric coupling effect with the tunnel magnetoresistance manipulated by ferroelectric polarizations, one of the most important results is that the exchange bias effect on the tunnel magnetoresistance is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 27 publications
1
23
0
3
Order By: Relevance
“…The resistance versus magnetic field curves, measured at 50 K and different polarizations of the ferroelectric layer, show clearly four distinct nonvolatile states. MFTJ and related physics of multiferroic junctions have been actively investigated both theoretically and experimentally . Recently, it was demonstrated that by further considering noncollinear magnetization alignments between the FM layers, MFTJ device with eight nonvolatile resistance states can be realized .…”
Section: Beyond Atomic 2d Semiconductorsmentioning
confidence: 99%
“…The resistance versus magnetic field curves, measured at 50 K and different polarizations of the ferroelectric layer, show clearly four distinct nonvolatile states. MFTJ and related physics of multiferroic junctions have been actively investigated both theoretically and experimentally . Recently, it was demonstrated that by further considering noncollinear magnetization alignments between the FM layers, MFTJ device with eight nonvolatile resistance states can be realized .…”
Section: Beyond Atomic 2d Semiconductorsmentioning
confidence: 99%
“…Due to these advantages, experimental efforts have been made and evidences of the four states have been demonstrated by several groups in MFTJs with (Ba, Sr)TiO 3 , BiFeO 3 , or PbZr 0.2 Ti 0.8 O 3 ferroelectric tunnel barriers. [15][16][17][18][19][20] Very recently, the realization of an epitaxial perovskite BaTiO 3 (BTO) based FTJ on silicon suggests the possibility of integrating FTJs/ MFTJs on silicon wafers, thus the integration with semiconductor electronics. 21 In addition to the capability to control electron and spin tunneling via ferromagnetic and ferroelectric polarizations in the electrode and barrier layers, the MFTJs have also been predicted to have other advantages beyond the simple addition of an MTJ with an FTJ.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if we set the turning fi eld to +60 Oe (green curve in Figure 2 b The junction resistance of the MFTJ could be further manipulated by ferroelectric polarization of barrier, displaying TER effect. [21][22][23][24][25][26] For the MFTJ, the ferroelectric polarization of the BaTiO 3 barrier can be aligned downward or upward by a poling voltage of +1.5 V or −1.5 V. As shown in Figure 4 , by a series of consecutive switching of the barrier polarization, the parallel resistances between the two polarization states 1 and 4 can be switched directly. To exclude other resistance switching mechanisms such as the interfacial electrochemical modifi cation or conducting fi lament formation and rupture, [ 37,38 ] piezoresponse force microscopy has been carried out to demonstrate that the ferroelectric polarization reversal is the underlying mechanism for the TER resistive switching in our system ( Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…[15][16][17] Similar to the multi ferromagnetic domain related multistates in MTJs, [12][13][14] multilevel memristor-type behavior can be obtained in ferroelectric tunnel junctions (tunnel junctions with ferroelectric barrier) as well by a partial switching of the ferroelectric domains in ferroelectric barrier. [18][19][20] [21][22][23][24][25][26][27] Combining these two mechanisms of increasing storage states, the multinary memory devices with an enhanced capacity of information storage may be achieved through integrating the features of noncollinear magnetization alignment with the ferroelectric polarization switching.…”
Section: Introductionmentioning
confidence: 98%